Omissão de impugnação das razões essenciais e uso meta-argumentativo avaliativo das razões acessórias nas sentenças da suprema corte de Buenos Aires - Cucatto, Mariana (2017)
In court argumentation, distinction can be made between those arguments which are essential or on which a decision is founded -ratio decidendi or holding-, and those which are not necessary to the result -further arguments ("a mayor abundamiento") or dicta-. This paper describes and explains, from a Cognitive Linguistic theoretical and methodological stance, how the Supreme Court of the Province of Buenos Aires dismisses those appeals which solely object further arguments and fail to attack the essential arguments on which the appealed decision is grounded, through the meta-argumentative evaluative use of further arguments. Such meta-cognitive use allows us to see the way in which the highest court in the Province of Buenos Aires plays a teaching role by showing how to distinguish between essential arguments from those which are not and how a judicial decision containing both essential and further arguments must be properly attacked.